2021
DOI: 10.3389/fnins.2021.654176
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Methods for the Detection of Tau Seeding Activity in Human Biofluids

Abstract: The ability of tau aggregates to recruit and misfold monomeric tau and propagate across brain regions has been studied extensively and is now recognized as a critical pathological step in Alzheimer’s disease (AD) and other tauopathies. Recent evidence suggests that the detection of tau seeds in human samples may be relevant and correlate with clinical data. Here, we review the available methods for the measurement of such tau seeds, their limitations and their potential implementation for the development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that the phosphorylated high-molecular-weight tau is responsible for tau propagation 62 , and we observed its increase in the cells co-exposed to blue light and nocodazole (see figure 4B and C). To test the promotable effect of the blue light-induced insoluble tau oligomers on tau seeding activity, a seed amplification assay 63,64 was carried out. Recombinant tau aggregation having a β-sheet structure was significantly increased by treatment of lysates from blue light-irradiated cells, compared with no irradiation (figure 5F).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the phosphorylated high-molecular-weight tau is responsible for tau propagation 62 , and we observed its increase in the cells co-exposed to blue light and nocodazole (see figure 4B and C). To test the promotable effect of the blue light-induced insoluble tau oligomers on tau seeding activity, a seed amplification assay 63,64 was carried out. Recombinant tau aggregation having a β-sheet structure was significantly increased by treatment of lysates from blue light-irradiated cells, compared with no irradiation (figure 5F).…”
Section: Resultsmentioning
confidence: 99%
“…In general, proteopathic seeds recruit, misfold, and template the aggregation of tau monomers, leading to their use in a wide range of seeding activity assays. So far, tau seeding activity can be quantified by in vitro seed amplification assays, such as Real-Time Quaking-Induced Conversion-based assay, RT-QuIC-based assay [ 12 , 46 ], cell-based assays in cultured cells, such as FRET-biosensor assay [ 31 ], and in vivo seed amplification assays [ 9 , 40 ]. Tau in AD and most other tauopathies is not mutated [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seeding activity of proteopathic tau has been evaluated by seed amplification assay in vitro, cell-based assay, and in vivo seed amplification assay [ 40 ]. Tau in AD and most tauopathies is not mutated [ 22 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tau seeding activity has been assessed by in vitro seed amplification assays, such as the Real-Time Quaking-Induced Conversion-based (RT-QuIC-based) assay ( Dujardin et al, 2020 ; Metrick et al, 2020 ), by cell-based assays in cultured cells, e.g., the fluorescence resonance energy transfer (FRET)-biosensor assay ( Holmes et al, 2014 ), and by in vivo seed amplification assays ( Clavaguera et al, 2009 ; Lathuiliere and Hyman, 2021 ). We previously found that truncated tau 151-391 is highly prone to being captured and templated to aggregation by oligomeric tau derived from AD brain (AD O-tau) ( Gu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%